2018
DOI: 10.20986/resed.2018.3695/2018
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidina como coadyuvante en bloqueos de nervio periférico

Abstract: Instrucciones de citación para el artículo / Citation instructions for the article: Rojas Gonzalez Andres. Dexmedetomidina como coadyuvante en bloqueos de nervio periférico / Dexmedetomidine as peripheral nerve block adjuvant. Rev. Soc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…15 Its addition in central neuraxial blocks and various nerve blocks has shown to decrease block latency, increase duration of motor block and period of analgesia. [16][17][18] Wang et al found that ropivacaine with dexmedetomidine in ESPB for modified radical mastectomy (MRM) was found to decrease VAS and analgesic consumption in the postoperative period when compared to plain ropivacaine without any adjunct. 19 Similar to dexmedetomidine, dexamethasone has also been in used in regional anaesthesia as additive for a very long period of time.…”
Section: Discussionmentioning
confidence: 99%
“…15 Its addition in central neuraxial blocks and various nerve blocks has shown to decrease block latency, increase duration of motor block and period of analgesia. [16][17][18] Wang et al found that ropivacaine with dexmedetomidine in ESPB for modified radical mastectomy (MRM) was found to decrease VAS and analgesic consumption in the postoperative period when compared to plain ropivacaine without any adjunct. 19 Similar to dexmedetomidine, dexamethasone has also been in used in regional anaesthesia as additive for a very long period of time.…”
Section: Discussionmentioning
confidence: 99%